Intrahepatic manifestation and distant extrahepatic disease in alveolar echinococcosis: a multicenter cohort study. (August 2021) - Graeter, Tilmann; Shi, Rong; Bao, Haihua; Liu, Wenya; Li, Weixia; Jiang, Yi; Schmidberger, Julian; Brumpt, Eleonore; Delabrousse, Eric; Kratzer, Wolfgang
Background: The main endemic areas of alveolar echinococcosis (AE) are in central Europe and western China. The infiltration of intrahepatic vascular and bile ducts as well as extrahepatic disease can lead to complications and may increase morbidity in AE. Purpose: To evaluate the vascular/biliary involvement of hepatic alveolar echinococcosis (HAE) and distant extrahepatic disease at each of four locations in Germany, France, and China. Material and Methods: Contrast-enhanced abdominal magnetic resonance imaging (MRI) scans of patients with HAE, 200 in total, were evaluated by five examiners. AE liver lesions were classified according to Kodama's classification. Furthermore, distant extrahepatic manifestations were documented with additionally performed imaging modalities. Vascular/biliary involvement of hepatic manifestations as well as the presence of extrahepatic manifestations were correlated with the respective Kodama type of the liver lesion. Results: Distant extrahepatic AE manifestations were significantly more frequent in China than in Europe (12/100 vs. 3/100; Fisher's exact test: P =0.0286). A significant relationship exists between presence of distant extrahepatic disease manifestation and size of the AE liver lesion (132.53 ± 48.65 vs. 92.49 ± 50.06; P = 0.0030). Vascular/biliary involvement is significantly more frequent in China than in Europe (86/100 vs. 65/100; χ 2 = 11.92; P = 0.0006). Vascular/biliary involvement depends on lesion size (111.10 ± 47.44 vs. 47.36 ± 24.36; P <0.0001). Different types of AE liver lesions are associated with differences in vascular/biliary involvement and extrahepatic manifestations. Conclusion: Vascular/biliary involvement and presence of distant extrahepatic manifestations depend on size of the HAE lesions and are more frequently detected in China. Different MRI morphological patterns influence vascular/biliary involvement and the occurrence of distant extrahepatic manifestations.